The use of GIS for agrochemical soil characteristics and weed infestation of Grebnevskiy nursery of Shchelkovskiy teaching and experimental forestry - O. V. Martynenko; V. N. Karminov; E. S. Yugaj; I. R. Mutygullin; P. V. Ontikov (Бюллетень Почвенного института им. В.В. Докучаева, 2019)
The article deals with the features of soil-agrochemical inspection of the nursery area with the use of geoinformation technologies. The purpose of this work was to conduct a soil survey of arable sod-podzolic medium - or light-loamy soils of the territory of the forest nursery, as well as estimation of production area contamination with weeds. The peculiarity of this study was the fact that the process of collection, systematization and processing of all compiled information was focused on the use of modern geographic information systems. Survey points were chosen in coordination with the administration of the nursery and were precised according to the actual space images. Geographical reference of testing points was carried out using global positioning technologies (GPS, GLONASS) based on the NextGIS mobile application (Android OS). Photofixation of nursery fields was performed by means of geotagging technologies, which allow implementation of the obtained graphic information directly into the geographic information system (GIS). The soil samples collected in the field were analyzed in the soil laboratory in order to determine the main indicators of soil fertility. On the basis of the received data the cartograms were developed by means of GIS, which provide information on the main nutrients content in the soil of nursery fields as well as on the most important indicators characterizing the soil absorbing complex (soil acidity, degree of base saturation, etc.). The study of weed infestation allowed developing the thematic map representing the weeds propagation on the nursery fields. All collected information was combined into a comprehensive geographic information system developed on the basis of Quantum GIS shell. As a result, the developed GIS will contribute to operational monitoring of soil fertility and ensure informational support for agricultural machinery applied in the nursery for growing planting material.